A Study of Delhi Sultanate and War Technology - Kumar, Naveen; Harshit (Innovative Research Thoughts, 2017)
Delhi had several Sultanates from the 12th to the 15th centuries. The Delhi Sultanate was founded after Muhammad Ghori defeated the Rajput king Prithviraj II in the battle of Tarain (second battle of Tarain) in 1192 AD. Qutbuddin Aibak became sultan of Delhi after the death of Ghori in 1206, and this formed the Slave dynasty. However, the Slave dynasty was finally overturned in 1290 AD when Qutbuddin Aibak's successor was overthrown. The Delhi Sultanate saw a steady succession of dynasties rising and fall: the Slave Dynasty lasted 1206 to 1290, the Khalji Dynasty lasted 1290 to 1320, the Tughluq Dynasty lasted 1320 to 1413, and the Sayyid Dynasty lasted 1414 to 1451. Ala Ud-din Khalji was the Khalji ruler under which the Muslim kingdom reached its zenith. When Tughluq's heirs began to break up the Delhi empire into many smaller states, it became almost difficult to bring it back together again.